Market institutions, transaction costs, and social capital in the Ethiopian grain market - Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 2001)
Using a New Institutional Economics framework, this research report addresses a fundamental aspect of markets: how do buyers and sellers find each other and coordinate the transfer of goods? The report quantifies the transaction costs related to search faced by traders in Ethiopia and analyzes the role of brokers in minimizing these transaction costs. The transaction costs of market search are significant in the Ethiopian grain market. Estimated as the opportunity cost of labor time spent searching for a trading partner and the opportunity cost of holding capital fixed during that search, these costs represent one-fifth of all marketing costs. This research report demonstrates that traders minimize their transaction costs of search by using brokers, who enable them to exchange with unknown partners. The report also shows that at the level of the grain economy as a whole, brokers significantly increase the total economic welfare by enabling a more efficient allocation of search effort by traders. Thus, traders with relatively higher search efficiency and lower search costs choose to search on their own, while traders with lower search efficiency and higher search costs choose to use a broker.